2020
DOI: 10.18546/rfa.04.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Patient and public involvement in a study of multimedia clinical trial information for children, young people and families

Abstract: There is increasing recognition of the need to involve the public in health research, but accounts of how best to achieve this are scarce. This article describes public involvement in the TRials Engagement in Children and Adolescents (TRECA) study, which is developing and evaluating multimedia information resources to inform children, young people and their familes about clinical trials. A dedicated group of young people with long-term health conditions and their parents met regularly throughout the study; fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…26 Hence, 147 (96.1%) participants were included in the analyses. 33 Participants were between 0 and 16 years old. The median age of the participants was 0.67 years (IQR 0.33, 3.75) and a higher proportion were male (62%).…”
Section: Resultsmentioning
confidence: 99%
“…26 Hence, 147 (96.1%) participants were included in the analyses. 33 Participants were between 0 and 16 years old. The median age of the participants was 0.67 years (IQR 0.33, 3.75) and a higher proportion were male (62%).…”
Section: Resultsmentioning
confidence: 99%
“…The TRECA MMI was developed through extensive qualitative research and user testing, where principles of participatory design were used to develop their style and format32–34 and informed by information design and principles of plain English,35 readability and age appropriateness. The TRECA PPI Group commented on the design and content of the MMI during their development 36…”
Section: Methodsmentioning
confidence: 99%
“…The TRECA PPI Group commented Open access on the design and content of the MMI during their development. 36 The MMI included five short video animations, each lasting 45-60 s (one specific to FORCE: 'Summary of the key aspects of the FORCE trial'; and four that were trial generic: 'Why do we do trials? '; 'What are trials?…”
Section: Development Of the MMImentioning
confidence: 99%
“…The TRECA study websites drew on extensive underpinning qualitative research ( Martin-Kerry et al, 2019 ) and user testing ( Sheridan et al, 2019 ), and were informed by principles of Plain English and information design ( Knapp et al, 2011 ), as well as age-appropriateness and readability formulae ( Readabilityformulas.com ). The TRECA Patient and Public Involvement Group commented on the content and design of the websites throughout their development ( Sheridan et al, 2020b ).…”
Section: Methodsmentioning
confidence: 99%
“…A higher DMQ score indicates better quality of decision-making. The DMQ comprised items evaluating aspects of trial participation decision-making indicated as important in the underpinning empirical work ( Martin-Kerry et al, 2017 , 2019 ; Sheridan et al, 2019 , 2020b ), including items on: information content; the experience of participation; uncertainty in trials; participation advantages and disadvantages; the process of decision-making; and decisional confidence. The nine scale items were followed by three free-text questions that asked respondents: to suggest any additional information they would have wanted; to identify aspects that were explained well; and for any other comments.…”
Section: Methodsmentioning
confidence: 99%